Sandokan in India: Facets of Nobility in Emilio Salgari’s Pirates of Malaysia Cycle - Feltrin-Morris, Marella; Freitag, Jason (Quaderni d'Italianistica)

(untitled) (Iter Press, 2025)
Much of the scholarly research produced on Emilio Salgari (1862–1911)—the creator of innumerable adventure novels featuring memorable characters such as the Malaysian pirate Sandokan and his imperturbable sidekick Yanez—has been dedicated to releasing him from the restrictive label of writer of young adult fiction, or, more recently, to measuring the degree of Orientalism or anti-colonialism in his portrayal of “exotic” locales and peoples. While not discarding the value of these approaches, this essay seeks to move in a different direction, and to examine instead the ways in which, by setting many of his stories in the Orient, and—in the case of the Pirates of Malaysia series—specifically in India, Salgari is able to interrogate questions of nobility, honour, loyalty, love, and morality.